Conceptual design of an amphibious e-tricycle - Atienza, Djovanni Karl D. (Animo Repository, 2022)
The lack of sustainable public transport, heavy traffic, and floods are some of the major problems that the Philippines are experiencing throughout the years. Fossil fuel is a limited source of energy and it contributes to the destruction of the ecosystem, which is why more sustainable alternatives are needed. In addition, heavy traffic makes it difficult for people to travel around the metro that eventually affects productivity, efficiency and causes unnecessary stress and sickness. Flooding has also claimed the lives of many people; some have died because they have drowned or because of the strong current of the flood, while some died due to slow response of rescuers because of extremely inaccessible paths. The research revolves around conceptualizing a three-wheeled electric vehicle with amphibious characteristics (waterproof electric motor, sealed body) to tackle the problems discussed earlier. A vehicle that will not be heavy on the budget which will make it accessible to most people; the problem with most amphibious or electric vehicles that exists today is that the features or specifications, or simply the build, is extremely high-tech and thus expensive and scarce. It will serve as a multipurpose vehicle for public utility/transportation, recreation, and or for emergency and rescue operations. The group believes that electricity is a better alternative than fossil fuels n consideration to climate change mitigation and adaptation. In addition, focusing on public transport that will carry multiple passengers would hopefully reduce current traffic and emissions.